Exploring Social Media’s Influence on Sustainable Indigenous Tourism - Abd Hamid, Zuliah; Johari, Shazali; Kunasekaran, Puvaneswaran (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to holistically understand the role of social media in influencing the sustainable ethnic tourism practice. An inductive approach is used to identify the level of the study variables. Past studies relevant towards social media technology and sustainability were analysed and discussed. It is evident that the existing literature heavily supports the need of social media in tourism development. Local communities especially the indigenous people are urged to utilize the virtual platform to sell their tourism products. However, unavailability of community capacity often hinder them to used social media at a desired level. Thus, a critical understanding of social media and sustainable tourism conceptualization is highlighted to provide a holistic perspective.